Spatio-temporal analysis of PM2.5 pollutant in Tehran metropolis during the years 2014-2017 - Saeed Motesaddizarandi; Rasul Nasiri (Mashhad University of Medical Sciences, 2020)
Background and Aim: Tehran, as the largest and most populous city in Iran, has encountered many problems, of which air pollution is the most common. In recent years, PM2.5 has been the cause of the unhealthiest days in terms of air pollution in Tehran; For this purpose, the present study was conducted with the aim of Spatio-temporal analysis of PM2.5 pollutant in the Tehran metropolis during the years 2014-2017 using GIS. Materials and Methods: In this study, Inverse Distance Weighting (IDW) and HotSpots methods have been used to predict and zoning of PM2.5 concentrations during four consecutive years (2014-2017). Results: The results of hotspot analysis and Getis-Ord-Gi index showed that the southern and southwestern regions with a confidence level above 90% and a concentration of more than 50 μg/m3 are the most polluted areas. And to a lesser extent, the western and central areas are next.; Also, the concentration of PM2.5 pollutants shows an increasing trend from north to south and east to west. Conclusion: South, southwest, west, and center are the most polluted areas; However, the present study only shows the zoning of PM2.5 concentration and does not identify the various factors and the contribution of each of them in the production of this pollutant; And it is necessary to conduct studies to identify sources and their contribution to control and reduce the concentration of PM2.5 in the Tehran metropolitan.